PEMBENTUKAN EMBRIO SOMATIK DARI EKSPLAN DAUN RAMIN, SPESIES TANAMAN LANGKA - Yelnititis Yelnititis (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2021)
Ramin (Gonystylus bancanus (Miq.) Kurz) is one of the most valuable timbers in Indonesia and the most over-exploited woody species, on the other hand, the success in propagation techniques are still limited. This species has been listed in Appendix II of CITES since 2004 as the number of trees and populations continuously decline. Tissue culture has been explored for mass propagation, however, this technique still faces the challenge, mainly in shoot elongation regenerated from single node explants. The purpose of these experiments is to select the best auxin (2,4-D, picloram, dan dicamba) and the best concentration of Benzyl Adenine (BA) treatment on somatic embryo formation. A series of experiments of somatic embryogenesis from leaf explant for ramin were conducted at Tissue Culture Laboratory, Center for Forest Biotechnology and Tree Improvement Yogyakarta. Modified Murashige and Skoog (MS) media supplemented with 0,1 mg/L thiamine; 0,5 mg/l nicotinic acid; 0,5 mg/L pyridoxine; 2.0 mg/L glycine and 100 mg/L myo-inositol were used as growth medium. In this study, three different auxins were used as treatments: 2,4-D (2,4 dichlorophenoxy acetic acid), picloram, and dicamba applied at 6.0 mg/L. The observation was made on the texture of callus formed and the performance of the somatic embryos obtained. The results showed that the texture of callus obtained is compact formed callus and green in color. The best treatment to induce globular somatic embryos is using 6.0 mg/L picloram within eight months. The best treatment to induce globular and torpedo somatic embryos is BA 3.0 mg/L treatment.